Application of steel fiber-reinforced cement-based grouting material in strengthening reinforced concrete beams exhibiting insufficient shear strength in historical buildings - Chen Zhouyi; Zhang Mingyu; Chen Wenyuan; Shi Jianguang (Case Studies in Construction Materials)
Effective reinforcement is necessary for the majority of historical buildings constructed with reinforced concrete. However, strengthening reinforced concrete components in historical buildings must adhere to the principle of ''minimal intervention''. On the one hand, the materials used for strengthening should be as compatible as possible with those of the original components. On the other hand, the shape and size of the strengthened components should not change significantly. A method utilizing steel fiber-reinforced cement-based grouting material (SFRCGM) in thin layers to strengthen reinforced concrete components of historical buildings was proposed, grounded in the principle of “minimal intervention”. The material used in this technology is cement-based material, which has similar properties to the original reinforced concrete components. Additionally, the minimum thickness of the strengthening layer in this technology can be as high as 10 cm, ensuring that the size of the original components is not significantly altered. To verify the feasibility of applying this method to strengthen reinforced concrete components in historical buildings, experimental research was conducted on the performance of eight shear-deficient RC beams strengthened using the proposed method. The shear failure observed in the reference beams was averted in the strengthened beams, which all experienced flexural failure due to a significant increase in their shear capacity. The use of 10 mm-thick strengthening layers and 20 mm-thick strengthening layers on both sides of the beams increased their shear capacity by 44.7 % and 89.6 %, respectively. When the expanded steel mesh was used in combination with 20 mm-thick strengthening layers, its shear capacity increased by 100.7 %. The devised predictive approach for ultimate loads in strengthened beams demonstrated reasonable accuracy.